Bahasa Arab Standard (Antara Âmmiyyah dan Fushah) - Yetti Hasnah (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2019)
Arabic Fusha is a language that is maintained and in principle same as Arabic which is used in the time of Jahiliya and the beginning of Islam. Whereas Arabic Amiya is Arabic has undergone many changes from the form of the Fusha, both from the aspect of vocabulary and structure. At the end of the 19th century there was an appeal to use Arabic Amiya as an oral and written language. The reason is because it is used by the Arab community in general and because of its simple form and structure. On the other hand, there are many defenders of Arabic Fusha who offer a number of weaknesses in Arabic Amiya as the reason for their rejection. In fact, both types of Arabic language still exist in Arabic society with their respective functions.